Probing GABA Receptor Function in Schizophrenia with Iomazenil - Ahn, Kyungheup; Gil, Roberto; Seibyl, John; Sewell, Richard Andrew; D'Souza, Deepak Cyril (Neuropsychopharmacology (New York, N.Y.), 2011)
Several lines of evidence from post-mortem, brain imaging, and genetic studies in schizophrenia patients suggest that Gamma-amino butyric acid (GABA) deficits may contribute to the pathophysiology of schizophrenia. Pharmacological induction of a transient GABA-deficit state has been shown to enhance vulnerability of healthy subjects to the psychotomimetic effects of various drugs. Exacerbating or creating a GABA deficit was hypothesized to induce or unmask psychosis in schizophrenia patients, but not in healthy controls. To test this hypothesis, a transient GABA deficit was pharmacologically induced in schizophrenia patients and healthy controls using iomazenil, an antagonist and partial inverse agonist of the benzodiazepine receptor. In a double-blind, randomized, placebo-controlled study, clinically stable chronic schizophrenia patients ( n =13) received iomazenil (3.7 μg administered intravenously over 10 min). Psychosis was measured using the Brief Psychiatric Rating Scale and perceptual alterations were measured using the Clinician Administered Dissociative Symptoms Scale before and after iomazenil administration. These data were compared with the effects of iomazenil in healthy subjects ( n =20). Iomazenil produced increases in psychotic symptoms and perceptual alterations in schizophrenia patients, but not in healthy controls. The greater vulnerability of schizophrenia patients to the effects of iomazenil relative to controls provides further support for the GABA-deficit hypothesis of schizophrenia.